2015
DOI: 10.1093/cvr/cvv218
|View full text |Cite
|
Sign up to set email alerts
|

A novel assay uncovers an unexpected role for SR-BI in LDL transcytosis

Abstract: We developed an assay to quantify LDL transcytosis across endothelial cells and discovered an unexpected role for SR-BI. Elucidating the mechanisms of LDL transcytosis may identify novel targets for the prevention or therapy of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 49 publications
5
149
2
Order By: Relevance
“…Recently, a novel method to assess LDL transcytosis using total internal reflectance microscopy (TIRF) was developed18 where the docking, fusion and transcytosis of LDL could be easily quantified in human coronary arterial endothelial cells (HCAEC) treated with PCSK9 to remove LDLR from the surface (see Supplementary Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a novel method to assess LDL transcytosis using total internal reflectance microscopy (TIRF) was developed18 where the docking, fusion and transcytosis of LDL could be easily quantified in human coronary arterial endothelial cells (HCAEC) treated with PCSK9 to remove LDLR from the surface (see Supplementary Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ALK1 has been localized to caveolae and may also contribute to reduced LDL uptake in Cav1 -knockout mice32. Most recently, the lipoprotein scavenger receptor for HDL, SR-B1, has been identified as a new candidate mediating the uptake and transcytosis of LDL in endothelial cells18. However, the loss of SR-B1 enhances atherogenesis, possibly by reducing hepatic HDL clearance33.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transport of LDL across endothelial cells has previously not attracted much attention, but recent studies have shown that SR-BI 8 and possibly caveolin-1 9 mediate LDL transcytosis and that this process is responsive to LDL levels in the blood. 10 The retention of LDL is mediated by positively charged amino acids in apolipoprotein B (the main protein moiety on LDL) that interact with negatively charged artery wall proteoglycans.…”
Section: See Accompanying Article On Page 49mentioning
confidence: 99%